Pelatihan Aplikasi Pembelajaran Matematika Pada Guru Sman 1 Dewantara - Ayu Ningtiyas, Fitri; Zahara, Yulia; Fajriana, Fajriana (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2024)
: A quality education can provide space for students to acquire relevant knowledge, useful skills, and character building needed to face challenges and competition in the future. Based on monitoring and interviews with teachers at SMAN 1 Dewantara, the mathematics learning process at the school has not maximized the use of learning applications during the learning process. In response to these problems, in this service activity, training on mathematics learning applications was carried out for teachers of SMAN 1 Dewantara with the aim of improving teacher skills and becoming a reference for teachers in maximizing student potential in using IT-based mathematics learning media. The training method is carried out with inquiry or direct practice so as to support the teacher's direct experience during the learning process.  The result of this service activity is that teachers are able to use math learning applications so that later it is hoped that this application can be used in the learning process.